THE EFFECT OF GIVING MORINGA LEAF EXTRACT (Moringa oleifera) THROUGH DRINKING WATER ON COMMERCIAL BROILER CARCASS CUTS - H.B., Wanti,; Candrawati, D.P.M.A; Sukmawati, N. M. S. (Jurnal Peternakan Tropika, 2024)
This study aims to examine the effect of administering Moringa leaf extract through drinking water on the percentage of commercial carcass cuts in broilers. The research used a Completely Randomized Design (CRD) with four treatments and four replications. Each replication involved four broilers, resulting in a total of 64 broilers. The treatments were P0 (broilers without Moringa leaf extract), P1 (broilers with 2% Moringa leaf extract), P2 (broilers with 4% Moringa leaf extract), and P3 (broilers with 6% Moringa leaf extract). The observed variables included carcass percentage, breast, wing, back, thigh, and drumstick percentages. The results showed that administering Moringa leaf extract (Moringa oleifera) through drinking water did not significantly affect (P>0.05) the weight of the cut, carcass weight, or the percentages of carcass, breast, wing, back, thigh, and drumstick. Based on these findings, it can be concluded that administering Moringa leaf extract (Moringa oleifera) through drinking water at levels of 2-6% does not affect the weight of the cut, carcass weight, carcass percentage, or the percentage of commercial cuts including breast, wing, back, thigh, and drumstick.